Improving Health Services and Redesigning Health Systems : Using Care Cascade Analytics to Identify Challenges and Solutions, Volume 1. Population-level Cascade Analytics - Fraser-Hurt, Nicole; Shubber, Zara; Ward, Katherine (World Bank, Washington, DC, 2022)
This practical, interactive guide walks health program implementers through how to use cascade analytics to improve service delivery and client outcomes. For policy-makers, it explains the power of the cascade framework as an analysis tool and how it can help identify bottlenecks and solutions, and inform quality improvements and in-service reforms for more efficient, client-centered services. Cascade analytics also offer a practical way to track progress and demonstrate the concrete impact that specific changes in service delivery have on outcomes. In applications, we have found that cascades provide a powerful visual summary of where care processes stall and impact is lost.  The guide helps readers master key concepts and guides them through the process of designing and conducting cascade analytics. It engages the reader and facilitates step-by-step learning with interactive features and real-life examples. The guide contains tried and tested templates for cascade analytics especially for non-communicable disease programs, and a worked example on hypertension care. The tools can also be used to better understand why clients are dropping out of care and what opportunities exist to bring them back and keep them in the program to attain their treatment targets.